2011
DOI: 10.1111/j.1582-4934.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 regulates ANF expression synergistically with Sp1 in a cardiac hypertrophy model

Abstract: Cardiac hypertrophy in response to multiple stimuli has important physiological and pathological significances. GATA4 serves as a nuclear integrator of several signalling pathways during cardiac hypertrophy. Sp1 and Sp3 are also reported to be involved in this process. However, the mechanism by which GATA4 acts as a mediator, integrating these ubiquitously expressed transcriptional factors, is poorly understood. We found that the expression of GATA4 and Sp1 was up-regulated in the myocardium of a pressure over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Thus, we have shown that Sp1 and GATA4 are upregulated in response to hypertrophic stimuli both in vitro and in vivo. These findings are consistent with a previous study 32 and similar to those of Azakie et al, 33 who reported that GATA4 and Sp1 protein levels are increased in a neonatal lamb cardiac shunt model of biventricular hypertrophy. These data suggest that the transcription factor activity of GATA4 and Sp1 exacerbates cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we have shown that Sp1 and GATA4 are upregulated in response to hypertrophic stimuli both in vitro and in vivo. These findings are consistent with a previous study 32 and similar to those of Azakie et al, 33 who reported that GATA4 and Sp1 protein levels are increased in a neonatal lamb cardiac shunt model of biventricular hypertrophy. These data suggest that the transcription factor activity of GATA4 and Sp1 exacerbates cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 93%
“…Both the promoters for ANP (NPPA) and the GC-A receptor (NPR1) have been shown to be regulated by Sp1 (Liang et al 1999, Kumar et al 2010, Hu et al 2011, and we, and others, have indicated a role for Sp1/Sp3 in controlling Nppc transcription in pituitary cell lines (Ohta et al 1993, Thompson et al 2009). The other major regulator of cGMP signaling is the gaseous neurotransmitter, nitric oxide (NO), and both neuronal and endothelial forms of the NO-synthesizing enzyme, NO synthase (NOS1 and NOS3, respectively), are transcriptionally controlled by Sp1 (Kleinert et al 1998, Bachir et al 2003.…”
Section: Endocrine-related Cancermentioning
confidence: 78%
“…Primers for atrial naturiuretic factor (ANF), Connexin 43 (Con43), Cardiac troponin I (cTnl; Tro I), cardiac Troponin T type 2 (Tnnt2; Tro II), NK2 homeobox 5 (Nkx2.5), Myocyte enhancer factor 2C (Mef2c) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were designed using the web-based "Primer 3" program. Primers for ß-cardiac myosin heavy chain (β-MHC), natriuretic peptide B (NPPB) and GATA binding protein 4 (GATA 4) were published previously [45,46]; as were the primers for Beta-2-microtubulin (B2M), TATA box binding protein (TBP) [47] and those for 18S ribosomal protein mRNA (18 sr RNA) [48]. The SYBR Green based qPCR mix was purchased from Peqlab (Erlangen, Germany).…”
Section: Gene Expressionmentioning
confidence: 99%